2010
DOI: 10.1111/j.1467-8535.2010.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy * technology: A two‐dimensional model for teachers' ICT integration

Abstract: This paper presents a two-dimensional model for measuring individual teachers' progression in ICT integration and for guiding them toward higher integration levels. There are four levels in the pedagogy dimension: direct teaching, cognitively active learning, constructive learning, and social learning. These levels are defined based on four factors: teacher pedagogical beliefs, instructional strategies used, teacher-student interactions, and the types of tasks students are expected to carry out. The technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 8 publications
4
59
1
4
Order By: Relevance
“…Among the roles particularly emphasized in the literature is the provision of pedagogical and personal support to students (Lin et al, 2012;Muñoz Carril, González Sanmamed, & Hernández Sellés, 2013;Rienties, Herodotou, Olney, Schencks, & Boroowa, 2018;Starčič & Vukan, 2019). Recent research among 72 000 students engaged in 74 courses indicated that 69% of weekly engagement by students were primarily determined by how online teachers designed online courses and how they supported their students (Nguyen, Rienties, Toetenel, Ferguson, & Whitelock, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the roles particularly emphasized in the literature is the provision of pedagogical and personal support to students (Lin et al, 2012;Muñoz Carril, González Sanmamed, & Hernández Sellés, 2013;Rienties, Herodotou, Olney, Schencks, & Boroowa, 2018;Starčič & Vukan, 2019). Recent research among 72 000 students engaged in 74 courses indicated that 69% of weekly engagement by students were primarily determined by how online teachers designed online courses and how they supported their students (Nguyen, Rienties, Toetenel, Ferguson, & Whitelock, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are unintended consequences of technology in the classroom (Coughlan, 2015;Harper & Milman, 2016). The ways teachers use technology make the difference between merely substituting traditional practices with digital forms and using technology to transform teaching by facilitating students' active construction of new understandings (Dolan, 2016;Groff & Mouza, 2008;Gundy & Berger, 2016;Lin, Wang, & Lin, 2012;Staples, Pugach & Himes, 2005;Tarling & Ng'ambi, 2016;Zhao et al, 2002).…”
Section: Ses and The Digital Use Dividementioning
confidence: 99%
“…Still other models of teacher learning and implementation progressions involve teachers in examining several factors simultaneously to self-asses as a part of their professional development. Lin, Wang, & Lin (2012) propose a two-dimensional model of ICT implementation which plots technical practices on one axis and pedagogical practices on the other. The pedagogical competencies ranged from direct teaching to constructivist learning.…”
Section: Lessons From Implementation: Drilling Down To Practicesmentioning
confidence: 99%
“…Se distinguen básicamente dos, una vinculada a un enfoque directivo que se manifiesta en prácticas de aula con un rol protagónico del docente y una actuación más bien pasiva del estudiante; mientras que la otra responde a un enfoque constructivista manifestada en prácticas de aula con un papel protagónico de los estudiantes y un rol mediador del docente (Ertmer et al, 2015;Lim & Chai, 2008). A esta clasificación, otros autores han agregado dos enfoques adicionales, el de aprendizaje activo y el de aprendizaje social (Lin, Wang & Lin, 2012).…”
Section: Creencias Pedagógicas Y Tecnologías Digitalesunclassified
“…Las respuestas al cuestionario fueron analizadas a partir de una adaptación al modelo bidimensional pedagógico-tecnológico de integración curricular de las tecnologías digitales, propuesto por Lin, Wang & Lin (2012). De esta manera, los docentes fueron clasificados de acuerdo a la intencionalidad pedagógica con la cual orientan sus clases, ubicándolos en una de cuatro creencias pedagógicas utilizadas como marco de análisis (tabla 2).…”
Section: Diseño De Investigaciónunclassified